Ancient Roman History and the Emergence of Medicine in Rome - Nabila; Eka Deviana Safitri (Yayasan Yusda Edu Indonesia, 2026)
Ancient Roman civilization is one of the most influential civilizations in world history, particularly in shaping the foundations of modern law, politics, culture, and goverment. This article aims to comprehensively examine the historycal journey of Ancient Rome from its inception, the development of the governmental system from kingdom to empire, the social, economic, political, and cultural life of Roman society, and the legancy of Roman civilization that is still felt today. The method used in this research is a literature study with a historycal-descriptive approach through the analysis of various classical and modern historical sources. The results of the study indicate that Rome's glory was determined not only by its military strength, but also by its geographical superiority, adaptive political system, organized social structure, and the Roman's ability to absorb and develop cultural elements from other civilizations. The conclusion of this study confirms that Ancient Rome made significant contributions to the development of Western civilization, particularly in the fields of law, state administration, language, engineering, and architecture. Therefore, understanding Ancient Roman history is essential as a foundation for understanding the development of the modern world..